PENGARUH KEPEMIMPINAN, DISAIN PEKERJAAN, DAN IKLIM ORGANISASI TERHADAP KEPUASAN KERJA TENAGA PENUNJANG AKADEMIK DI UNIVERSITAS NEGERI MEDAN - Irsan Irsan (Universitas Negeri Jakarta, 2011)
The objectives of this research were to find out: (1) the effect of leadership on job satisfaction, (2) the effect of job design job satisfaction, (3) the effect of organizational climate on job satisfaction; (4) the effect of leadership on organizational climate; and (5) the effect of job design on organizational climate. The study was a survey conducted in Medan with 79 sample of Medan University employees, selected randomly. The data were analyzed by using path analysis. The result of this research were as follows: (1) there was a positive effect of leadership on job satisfaction; (2) there was a positive affect of job design on job satisfaction; (3) there was a positive effect of organizational climate on job satisfaction; (4) there was a positive effect of leadership on organizational climate; and (5) there was a positive effect of job design on organizational climate. In order to improved job satisfaction, leadership in line with context and situation, the relevant job design, and the conducive organizational climate should be put into human capital management; however other variables were necessary to be taken into account by next job satisfaction research.